Faktor-faktor yang Mempengaruhi Kepatuhan Ibu dalam Pemberian Imunisasi Difteri pada Balita - Muklati, Ameylia Hilda; Rokhaidah, Rokhaidah (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2020)
Immunization is prevention efforts to increase a person's immunity to several diseases that can be prevented by immunization (PD3I), specifically Diphtheria Pertusis Tetanus (DPT). This study aims to analyze the relationship of mother’s characteristics (age, education, employment), mother’s knowledge, maternal attitudes, beliefs of mother and family support with compliance in the provision of diphtheria immunization to toddlers. This study uses quantitative analytics with Cross-Sectional design with a puposive sampling technique and obtained 75 respondents. Respondents this study of a mother having a toddler (aged 1-5 years) in RW 01, Kukusan Village, Beji Sub-District, Depok City. The instruments used are primary data (questionnaire and observation) and secondary data (KMS/KIA books). Analysis of the data used is the bivariate statistical with the Chi-Square method. The results showed that there is a relation between age (p=0.008), education (p=0,000), employment (p=0.003), mother’s knowledge (p=0.001), maternal attitudes (p=0.001), beliefs of mother (p=0.003) and family support (p=0,000) with maternal compliance in the provision of diphtheria immunization to toddlers in RW 01 Kukusan Village, Beji Sub-District, Depok City. The researchers recommend health education about immunization to mothers to improve compliance in providing children immunizations.